2015
DOI: 10.7439/ijbr.v6i3.1804
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Rotavirus Infection in Children Less than Five Years in Omdurman Paediatric Hospital, Khartoum, Sudan

Abstract: Objective: Our objective is to study epidemiology of rotavirus infection in children less than five years during one year in Omdurman Paediatric Hospital. Materials and Methods:The study design was a setting-based study. The required data were obtained by reviewing records of a year in the hospital. Results: The findings revealed that, the total cases of rotavirus infection was 1563, majority of cases occurred among age group 1-12 months 642(41%). About 899(57.5%) of cases were males while 664(42.5%) were fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…In this study, the minimum age of infected children was (1) months while maximum age was seven years and the mean age was 1.23 years. The reported age come in line with that reported in local [13] and international studies in Sudan [2], India [14] and Taiwan [15]. In the current study, males represent (62.5%) which come by findings in Iraq [13,16], India [14], and Sudan [2].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this study, the minimum age of infected children was (1) months while maximum age was seven years and the mean age was 1.23 years. The reported age come in line with that reported in local [13] and international studies in Sudan [2], India [14] and Taiwan [15]. In the current study, males represent (62.5%) which come by findings in Iraq [13,16], India [14], and Sudan [2].…”
Section: Discussionsupporting
confidence: 91%
“…The reported age come in line with that reported in local [13] and international studies in Sudan [2], India [14] and Taiwan [15]. In the current study, males represent (62.5%) which come by findings in Iraq [13,16], India [14], and Sudan [2]. The minimum CRP level (6 mg/dl), the maximum was (96 mg/dl) and the mean (31.72 ± 30.58 mg/dl).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In Sudan, viral genotyping was studied based on the viral proteins (VP4 and VP7) by nested PCR and gene sequencing results showed the VP7 predominant G class was G1 (8). Two epidemiological studies conducted on under-5-year-old children infected with rotavirus in Omdurman Pediatric Hospital, Sudan; The first was a setting-based study over one year, which concluded that rotavirus represents a public health problem among Sudanese children younger than five years and that effective control procedures are essential to reduce this problem (9). The other study found that rotavirus prevalence was 25% in children under the age of five, and that rotavirus vaccine, accurate and routine diagnosis of acute child diarrheal infection aids in accurate management, preventing antibiotic use, and reducing the prevalence in vulnerable children (10).…”
Section: Foodborne Viral Situation In Sudan 131 Rotavirusmentioning
confidence: 99%